Endovascular Strategies in the Management of Acute Limb Ischemia - Lind, Benjamin (Vasc Specialist Int, 2019)
Acute limb ischemia (ALI) represents one of the most common emergent scenarios encountered by a vascular specialist. Despite expedient revascularization, high rates of limb loss are reported along with high mortality rates which are second only to ruptured abdominal aortic aneurysms. Surgical revascularization is standard of care. Endovascular techniques as an alternative have emerged to be appropriate first line therapy when addressing the threatened limb. We review the etiology and classification of ALI and current endovascular techniques and evidence to date in the management of patients acutely presenting with extremity ischemia.